Diaphragm for water electrolysis

The laminate structure of a porous polyethylene film with hydrophilic groups and a polyarylene sulfide support, bonded with styrene butadiene rubber, addresses the challenges of maintaining ion permeability and durability in alkaline water electrolysis, ensuring efficient and reliable operation.

JP2025040452APending Publication Date: 2025-03-25TORAY INDUSTRIES INC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023147268
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-12
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

Existing diaphragms for alkaline water electrolysis face challenges in maintaining high ion permeability and durability in high-temperature, high-concentration alkaline aqueous solutions, leading to potential short circuits and separation issues during maintenance.

Method used

A laminate structure comprising a porous polyethylene film with chemically bonded hydrophilic groups and a porous support made of polyarylene sulfide, bonded with styrene butadiene rubber, which enhances ion permeability and interlayer adhesion while resisting alkaline conditions.

Benefits of technology

The laminate achieves high ion permeability and durability, preventing short circuits and maintaining structural integrity even in harsh alkaline conditions, thus ensuring efficient and reliable operation of alkaline water electrolysis devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025040452000001
    Figure 2025040452000001
  • Figure 2025040452000002
    Figure 2025040452000002
Patent Text Reader

Abstract

To provide a laminated body composed of a porous film and a porous support having high ion permeability, durability with ion permeability even in an alkali aqueous solution with high temperature and high concentration, and durability with interlayer adhesion strength.SOLUTION: Provided is a laminated body where a porous film made of polyethylene is jointed with a porous support having a principal component of a polyarylene sulfide. On a surface or a pore surface of the porous film, a hydrophilic group including at least one of a hydroxy group and a carboxyl group is chemically bonded with the polyethylene. A ratio (content B / content A) of a content B of the hydrophilic group included in the entire porous film to a content A of carbon atom included in the entire porous film is larger than a ratio (content D / content C) of a content D of the hydrophilic group on a surface part composed of both sides of the porous film to a content C of carbon atom on the surface part composed of both sides of the porous film. The ratio (content B / content A) is 0.03 to 0.20. The ratio (content D / content C) is 0.01 to 0.10. The porous support is bonded to the porous film with a styrene-butadiene rubber.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a diaphragm for water electrolysis. [Background technology]

[0002] Alkaline water electrolysis is a water electrolysis method that can produce hydrogen inexpensively without using expensive metal catalysts. As hydrogen has recently been attracting attention as an alternative resource to petroleum, attention to alkaline water electrolysis has also been rapidly increasing.

[0003] In alkaline water electrolysis, a diaphragm is usually used to separate the cathode and anode, and the diaphragm is required to have high ion permeability in order to reduce the voltage required to operate the water electrolysis device. In addition, the diaphragm is also required to have high gas barrier properties in order to prevent the problem of oxygen gas generated at the anode being mixed with hydrogen gas generated at the cathode as a result of water electrolysis, resulting in a decrease in the purity of the hydrogen gas.

[0004] In order to meet the above-mentioned requirements for membranes, such as high ion permeability and high gas barrier properties, various inventions have been made to date. For example, Patent Document 1 discloses a method for obtaining a membrane with ion permeability by graft polymerizing a monomer having an ion-exchangeable functional group onto a porous film. In this invention, the polymer forming the porous film is made to swell in an electrolyte solution to exhibit gas barrier properties.

[0005] On the other hand, in order to reduce the voltage required to operate a water electrolysis device, in addition to the characteristics of the diaphragm, efforts have been made to change the design of the device itself, and as one such design, a zero-gap structure in which the cathode and anode are in direct contact with the diaphragm has become widespread. However, in a zero-gap structure, there is a risk that the diaphragm will be damaged by contact with the electrodes, causing a short circuit in the device, and as a countermeasure, it has been considered to protect the surface of the porous film as described above with a support. For example, Patent Document 2 discloses a method of suppressing short circuits by arranging a porous support on one or both sides of a porous film. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2014-148709 A [Patent Document 2] JP 2014-148708 A Summary of the Invention [Problem to be solved by the invention]

[0007] However, in the alkaline water electrolysis, a high-concentration alkaline aqueous solution (30 wt% potassium hydroxide aqueous solution or sodium hydroxide aqueous solution) is used as the electrolyte to obtain high ion conductivity, and the electrolysis rate is increased to a high temperature of about 80 to 90°C. Therefore, in the method of graft polymerizing a monomer having an ion-exchangeable functional group onto a porous film as described in Patent Document 1, depending on the type of graft polymer component, the graft polymer component cannot withstand the harsh environment, and the graft polymer component is lost from the porous film over time, resulting in the porous film losing its ion permeability. In addition, in the method of disposing a porous support on one or both sides of a porous film as described in Patent Document 2, unless a binder material that is resistant to the high-temperature and high-concentration alkaline aqueous solution is selected as the binder material used to bond the porous film and the porous support, the bond between the porous film and the porous support will be loosened during use, and therefore, when the diaphragm is recovered from the device during maintenance of the alkaline water electrolysis device, the two will separate, making handling complicated.

[0008] In view of the above problems, the present invention aims to provide a laminate consisting of a porous film and a porous support, which has high ion permeability and further has durability of ion permeability and shape retention even in a high-temperature and high-concentration alkaline aqueous solution. [Means for solving the problem]

[0009] In order to solve the above problems, the present invention provides a laminate having the following configuration: (1) A laminate comprising a porous film made of polyethylene and a porous support mainly composed of polyarylene sulfide, wherein hydrophilic groups containing at least one of a hydroxyl group and a carboxyl group are chemically bonded to the polyethylene on the surface and pore surfaces of the porous film, the ratio of the content B of the hydrophilic groups contained in the entire porous film to the content A of the carbon atoms contained in the entire porous film (content B / content A) is greater than the ratio of the content D of the hydrophilic groups in the surface portions constituting both sides of the porous film to the content C of the carbon atoms in the surface portions constituting both sides of the porous film (content D / content C), the ratio (content B / content A) being 0.03 to 0.20, and the ratio (content D / content C) being 0.01 to 0.10, and the porous support and the porous film being bonded with styrene-butadiene rubber; (2) The laminate according to (1), wherein the porous film contains a surfactant, and the reduction rate of the surfactant before and after immersing the porous film in hot water at 80° C. for 100 hours is 10% or less. (3) The laminate according to (2), wherein the surfactant is a polyoxyalkylene alkyl ether. (4) The laminate according to any one of (1) to (3), wherein the styrene-butadiene rubber has a glass transition temperature of −30° C. or lower. Effect of the Invention

[0010] According to the present invention, it is possible to provide a laminate comprising a porous film and a porous support, which has high ion permeability, and further has durability of ion permeability and interlayer adhesion even in a high-temperature and high-concentration alkaline aqueous solution. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The laminate of the present invention will be described in detail below. The laminate of the present invention is a laminate in which a porous film made of polyethylene and a porous support mainly composed of polyarylene sulfide are laminated. In the porous film, hydrophilic groups containing at least one of hydroxyl groups and carboxyl groups are chemically bonded to the polyethylene constituting the porous film on the surface and pore surfaces. The ratio of the content B of the hydrophilic groups contained in the entire porous film to the content A of carbon atoms contained in the entire porous film (content B / content A) is greater than the ratio of the content D of the hydrophilic groups in the surface parts constituting both sides of the porous film to the content C of carbon atoms in the surface parts constituting both sides of the porous film (content D / content C), the ratio (content B / content A) being 0.03 to 0.20, and the ratio (content D / content C) being 0.01 to 0.10. The porous support and the porous film are bonded with styrene butadiene rubber.

[0012] <Porous film> The porous film used in the laminate of the present invention has many fine through-holes. In the water electrolysis process, ions pass through the many through-holes in the porous film. The average pore size of the pores in the porous film of the present invention is preferably 15 to 100 nm, more preferably 20 to 50 nm. When the average pore size is 15 nm or more, ions can be smoothly passed through. On the other hand, when the average pore size is 100 nm or less, mixing of oxygen and hydrogen generated in the water electrolysis process can be suppressed.

[0013] The porosity of the porous film is preferably 20 to 70%, and more preferably 30 to 60%. When the porosity is 20% or more, ions can be smoothly transmitted. On the other hand, when the porosity is 70% or less, the porous film can have sufficient mechanical strength.

[0014] The thickness of the porous film is 5 to 30 μm, and more preferably 10 to 20 μm. By making the thickness of the porous film 20 μm or less, ion permeation can be performed smoothly. On the other hand, by making the thickness of the porous film 5 μm or more, the porous film can maintain a strength that can withstand heat and tension when fiber materials mainly composed of polyarylene sulfide are bonded to form a laminate.

[0015] The porous film is made of polyethylene. Here, polyethylene refers to a polymer having ethylene as a monomer, but may also be copolymerized with small amounts of other monomer components such as propylene, 1-butene, 1-pentene, and 3-methylpentene-1, as necessary.

[0016] <Hydrophilic group> In addition, the porous film has hydrophilic groups containing at least one of a hydroxyl group and a carboxyl group chemically bonded to polyethylene on the surface and pore surface. The presence of the hydrophilic groups on the surface and pore surface of the film makes the electrolyte more compatible with the film, and allows ions to pass through smoothly. In addition, the ion permeability of the laminate obtained by graft polymerizing a monomer having a hydroxyl group or a carboxyl group on the surface and pore surface of the porous film or impregnating a polymer having a hydroxyl group or a carboxyl group into the porous film is gradually lost due to the lack of durability of the graft polymerization component or the impregnated polymer component in a high-temperature and high-concentration alkaline aqueous solution, but in the present invention, the hydrophilic group containing at least one of a hydroxyl group and a carboxyl group is chemically bonded directly to polyethylene, so that the laminate can have durability of ion permeability even in a high-temperature and high-concentration alkaline aqueous solution.

[0017] The ratio of the content B of the hydrophilic groups contained in the entire porous film to the content A of the carbon atoms contained in the entire porous film (content B / content A) is greater than the ratio of the content D of the hydrophilic groups in the surface portion constituting both sides of the porous film to the content C of the carbon atoms in the surface portion constituting both sides of the porous film (content D / content C). As a result, the ratio of hydrophilic groups in the wall surface of the pores of the porous film is greater than the ratio of hydrophilic groups in the surface portion of the porous film. That is, the wettability of water in the wall surface of the pores is greater than the wettability of water in the surface portion, and as a result, the water in contact with the surface portion is easily drawn into the inside of the pores, and it is considered that the porous film of the present invention can exhibit very high ion permeability. Here, the surface portion refers to a depth of 10 nm or less from the surface constituting both sides of the porous film.

[0018] In the porous film, the ratio (content B / content A) of the content B of the hydrophilic group contained in the entire porous film to the content A of the carbon atoms contained in the entire porous film is 0.03 to 0.20. When the (content B / content A) is in the above range, the porous film used in the present invention exhibits sufficient ion permeability and mechanical strength, and can hold water in the pores via the hydrophilic groups, thereby suppressing the mixing of oxygen and hydrogen generated in the water electrolysis method. In addition, the preferable range of the (content B / content A) is 0.05 to 0.17. When the (content B / content A) is 0.05 or more, the wettability of water on the surface of the pores of the porous film becomes better, higher ion permeability can be exhibited, and the mixing of oxygen and hydrogen generated in the water electrolysis method can be further suppressed. On the other hand, when the (content B / content A) is 0.17 or less, the scission of the polyethylene main chain that occurs when introducing a hydroxyl group or a carboxyl group into the polyethylene constituting the porous film is further suppressed, and the mechanical strength of the porous film used in the present invention can be maintained higher.

[0019] In addition, the ratio (content D / content C) of the content D of the hydrophilic group in the surface portion constituting both sides of the porous film to the content C of the carbon atoms in the surface portion constituting both sides of the porous film is 0.01 to 0.10. When the (content D / content C) is in the above range, the porous film used in the present invention exhibits sufficient ion permeability and mechanical strength. In addition, the preferred range of the (content D / content C) is 0.02 to 0.07. When the (content D / content C) is 0.02 or more, the porous film used in the present invention can suppress water repellency at the surface portion and exhibit higher ion permeability. On the other hand, when the (content D / content C) is small, such as 0.07 or less, scission of the polyethylene main chain that occurs when introducing hydroxyl groups or carboxyl groups into the polyethylene constituting the porous film is suppressed, and the mechanical strength of the porous film used in the present invention can be maintained higher.

[0020] <Surfactant> The porous film preferably further contains a surfactant. When the porous film contains a surfactant, the wettability of water is improved on the surface of the porous film and the wall of the pores, so that the porous film can exhibit high water permeability. The surfactant is preferably contained on the wall of the pores of the porous film. When the surfactant is contained on the wall of the pores, the wettability of water to the wall of the pores is improved, and water that comes into contact with the surface of the porous film is easily drawn into the pores, resulting in excellent ion permeability of the porous film.

[0021] In addition, it is preferable that the surfactant reduction rate is 10% or less before and after immersing the porous film in hot water at 80° C. for 100 hours, because when the laminate of the present invention is used for alkaline water electrolysis, contamination inside the device due to outflow of the surfactant component can be suppressed. In order to make the surfactant reduction rate 10% or less, it is preferable that the surfactant is contained in a chemically bonded state in the resin component constituting the porous film. By chemically bonding the surfactant to the resin component constituting the porous film, the surfactant is suppressed from dissolving in water when the porous film comes into contact with water, and as a result, the surfactant reduction rate can be made 10% or less before and after immersing the porous film in hot water at 80° C. for 100 hours.

[0022] The type of surfactant that can be used in the present invention is not particularly limited, and any of cationic, anionic, amphoteric, and nonionic surfactants can be used. Among them, nonionic surfactants are preferred because they have high permeability into the pores of the porous film, little foaming, and are easy to handle in the manufacturing process. Examples of nonionic surfactants include glycerin fatty acid esters, sorbitan fatty acid esters, sucrose fatty acid esters, polyoxyethylene alkyl ethers, polyoxyethylene alkylphenyl ethers, polyoxyethylene polyoxypropylene glycols, fatty acid polyethylene glycols, fatty acid polyoxyethylene sorbitan, and fatty acid alkanolamides. Among them, polyoxyethylene alkyl ethers are particularly preferred because they have high permeability into the pores of the porous film, little foaming, and are easy to handle in the manufacturing process.

[0023] <Porous support> The porous support of the present invention is mainly composed of polyarylene sulfide. By using polyarylene sulfide as the main component, durability can be exhibited even in a high-temperature and high-concentration alkaline aqueous solution, and the shape of the support can be maintained.

[0024] Examples of polyarylene sulfide include those having an arylene group with a skeleton such as o-phenylene, m-phenylene, or p-phenylene, among which, from the viewpoint of processability and industrial availability, polyphenylene sulfide having an arylene group of p-phenylene is preferred. Examples of the form of the porous support include woven fabric, nonwoven fabric, net, mesh, sintered porous membrane, etc., among which, from the viewpoint of handling when the porous support is bonded to a porous film to form a laminate and shape retention when immersed in a high-temperature high-concentration alkaline aqueous solution, woven fabric is preferred.

[0025] The porous support has a basis weight of 50 to 300 g / m 2 and more preferably 100 to 200 g / m 2 The basis weight of the porous support is 300 g / m 2 By setting the weight of the porous support to 50 g / m or less, ion permeation can be achieved smoothly. 2 By setting the thickness or more, the porous support can maintain a sufficient strength, and the phenomenon in which the porous film is damaged due to contact with the electrodes can be suppressed.

[0026] The porous support has an aperture ratio of 20 to 80%, and more preferably 30 to 70%. By setting the aperture ratio of the porous support to 80% or less, the phenomenon in which the porous film is damaged by contact with the electrode can be suppressed. On the other hand, by setting the aperture ratio of the porous support to 20% or more, ion permeation can be performed smoothly.

[0027] <Styrene butadiene rubber> The porous film and the porous support of the present invention are bonded with styrene-butadiene rubber, which exhibits high resistance to alkali, and therefore can maintain the bonded configuration of the porous film and the porous support even in a high-temperature and high-concentration aqueous alkali solution.

[0028] Furthermore, the styrene butadiene rubber preferably has a glass transition temperature of -30°C or lower. By having a glass transition temperature of -30°C or lower, the toughness as a binder is increased, and the shape retention can be further improved. From the viewpoint that the higher the toughness, the higher the shape retention can be improved, the glass transition temperature is more preferably -50°C or lower.

[0029] The coating amount of the styrene butadiene rubber is 1 to 10 g / m 2 and more preferably 1 to 5 g / m 2 The coating amount is 10 g / m 2 By setting the coating amount to 1 g / m or less, ion permeation can be performed smoothly. 2 By setting the above, the shape retention of the porous film and the porous support can be made sufficient.

[0030] <Method of manufacturing laminate> First, the method for producing the porous film of the present invention will be described. In the production of the porous film of the present invention, it is preferable to include a step of exposing a porous film made of polyethylene (hereinafter referred to as a polyethylene porous film) to a mixed gas of fluorine and oxygen. By exposing the polyethylene porous film to a mixed gas of fluorine and oxygen, the polyethylene chains are partially cut on the surface of the polyethylene porous film and on the wall surfaces of the pores by the corrosive action of the fluorine gas, and the polyethylene porous film is in a state in which other elements and functional groups can be bonded, that is, in an active state. By contacting the polyethylene porous film in the active state with an aqueous solution containing a surfactant, a polyethylene porous film can be obtained in which hydrophilic groups are chemically bonded to the sites where chemical bonds are cut by the treatment with the fluorine gas.

[0031] The above-mentioned mixed gas and the method of exposing the porous material will be described below.

[0032] The partial pressure of the fluorine gas in the mixed gas is preferably 0.1 to 0.2 atm, more preferably 0.13 to 0.16 atm. By setting the partial pressure of the fluorine gas within the above-mentioned range, the fluorine gas reacts sufficiently with the polyethylene porous film, and the chemical bond of the polyethylene is easily broken on the surface part of the polyethylene porous film and the wall surface of the pores, and further, the reaction between the polyethylene porous film and the fluorine gas is prevented from proceeding excessively, so that the mechanical strength of the polyethylene porous film is excellent.

[0033] The partial pressure of the oxygen gas in the mixed gas is preferably 0.3 to 0.8 atm, more preferably 0.5 to 0.6 atm. By setting the partial pressure of the oxygen gas within the above range, it is possible to suppress the hydrophobic fluorine element from bonding to the site where the chemical bond of the polyethylene is broken, and to increase the hydrophilicity of the polyethylene porous film.

[0034] In addition, the time for exposing the polyethylene porous film to the mixed gas, i.e., the time for treating the polyethylene porous film with the mixed gas, can be appropriately selected according to the use of the polyethylene porous film. Specifically, the above treatment time is preferably 5 seconds or more and 30 seconds or less, more preferably 15 seconds or more and 30 seconds or less. By making the above treatment time 5 seconds or more, the reaction between the polyethylene porous film and the mixed gas is sufficient. On the other hand, by making the above treatment time 30 seconds or less, in addition to excellent productivity, the reaction between the polyethylene porous film and the mixed gas can be suppressed from proceeding excessively, and the mechanical strength of the obtained polyethylene porous film is excellent.

[0035] In the method for producing a porous film of the present invention, it is preferable to include a step of exposing the polyethylene porous film to a mixed gas of fluorine and oxygen, and then immersing it in an aqueous solution containing a surfactant. As described above, by exposing the polyethylene porous film to a mixed gas of fluorine and oxygen, the chemical bonds of the polyethylene are partially broken and the film is activated. By immersing the activated polyethylene porous film in an aqueous solution containing a surfactant, the aqueous solution containing the surfactant penetrates into the pores of the polyethylene porous film. The water or surfactant contained in the aqueous solution containing the surfactant that penetrates into the activated polyethylene porous film comes into contact with the part of the polyethylene porous film in which the chemical bonds of the polyethylene are partially broken, and the hydrophilic group or surfactant component is bonded to obtain a polyethylene porous film having ion permeability. As described above, the surfactant is preferably polyoxyethylene alkyl ether.

[0036] The surfactant concentration in the aqueous solution containing the surfactant is preferably 0.10 to 1.00 mass%, more preferably 0.10 to 0.50 mass%. When the surfactant concentration is equal to or higher than the lower limit of the preferred range, the wettability of the solution containing the surfactant to the surface of the polyethylene porous film and the wall surface of the pores is improved, and hydrophilic groups and surfactant components are easily bonded. On the other hand, when the surfactant concentration is equal to or lower than the upper limit of the preferred range, for example, when used in alkaline water electrolysis, contamination inside the device due to outflow of surfactant components can be suppressed.

[0037] It is preferable to wash the polyethylene porous film with water after immersing the film in an aqueous solution containing a surfactant. By washing the film with water, the surfactant component that is excessively attached during the process of immersing the film in the aqueous solution containing a surfactant can be removed. The time for washing the film with water is not particularly limited, but it is preferable to wash the film with water for 10 seconds or more and 180 seconds or less from the viewpoint of productivity.

[0038] After washing the polyethylene porous film with water, it is preferable to remove moisture in a drying process. In this case, the drying temperature must be equal to or lower than the melting point of the polyethylene porous film, and is preferably equal to or lower than 80° C., and more preferably equal to or lower than 60° C. By setting the drying temperature to the above-mentioned preferred temperature or lower, deformation of the resulting polyethylene porous film due to thermal shrinkage can be suppressed.

[0039] Next, the porous film obtained by the above-mentioned production method and a porous support mainly composed of polyarylene sulfide are bonded together with styrene-butadiene rubber to obtain the laminate of the present invention.

[0040] When the porous support and the porous film are joined with styrene butadiene rubber, it is preferable to coat the porous support with an aqueous solution in which styrene butadiene rubber is dispersed. By coating the aqueous solution containing styrene butadiene rubber on a porous support having a high opening ratio, it is possible to suppress the phenomenon in which the styrene butadiene rubber forms a uniform film and blocks the permeation of ions when removing moisture. The aqueous solution containing styrene butadiene rubber can be coated on the porous support by knife coating, comma coating, gravure coating, dipping, etc. In this way, the porous support coated with styrene butadiene rubber is superimposed on one side of the porous film to be integrated, and then the moisture contained in the aqueous styrene butadiene solution is removed by drying in a dryer.

[0041] From the viewpoint of the heat resistance of the polyethylene porous film, the drying temperature at this time is preferably 50 to 80° C. Subsequently, a porous support coated with a styrene-butadiene aqueous solution in the same manner is laminated on the other side of the porous polyethylene film to be integrated, and then the film is dried in a dryer at 50 to 80° C. to remove the moisture contained in the styrene-butadiene aqueous solution, thereby obtaining the laminate of the present invention. EXAMPLES

[0042] The present invention will now be described in more detail with reference to examples. The property values ​​shown in the examples were measured by the following methods.

[0043] A.Hydrophilic group (1) Carbon atom content A in the entire porous film The carbon atom content A contained in the entire porous film was measured by X-ray photoelectron spectroscopy (XPS / ESCA). The porous film sample was cut obliquely by a cryomicrotome method to prepare the film cross section, and then introduced into the XPS device. The carbon atom content A was calculated from the C1s peak area ratio of the obtained spectrum.

[0044] The measurement conditions for the X-ray photoelectron spectroscopy (XPS / ESCA) are as follows: XPS equipment: ULVAC-PHI PHI-Quantera II X-ray source: AlKα, monochrome 1486.6eV, 25W ·Analysis area: 100μmΦ.

[0045] (2) Type and content of hydrophilic groups contained in the entire porous film B Two samples of the porous film were prepared, and one of the samples was subjected to gas-phase chemical modification using trifluoroacetic anhydride to label the hydroxyl groups contained in the sample. The sample with the hydroxyl groups labeled was introduced into the XPS device in the same manner as in (1) above, and when an F1s peak was detected, it was determined that the porous film contained hydroxyl groups. Next, when the porous film contained hydroxyl groups, the content of hydroxyl groups was calculated from the F1s peak area ratio of the obtained spectrum.

[0046] On the other hand, the other specimen was subjected to gas phase chemical modification using trifluoroethanol to label the carboxyl groups contained in the specimen. The specimen with the carboxyl groups labeled was introduced into the XPS apparatus in the same manner as in (1) above, and when the F1s peak was detected, it was determined that the porous film contained carboxyl groups. Next, when the porous film contained carboxyl groups, the content of carboxyl groups was calculated from the F1s peak area ratio of the obtained spectrum.

[0047] The total of the hydroxyl group content and the carboxyl group content was taken as the hydrophilic group content B contained in the entire porous film.

[0048] (3) The carbon atom content C in the surface portion of the porous film The porous film was cut to an arbitrary size and was measured in the same manner as in (1) above, except that it was introduced into the XPS device, and the content C was calculated.

[0049] (4) Content D of hydrophilic groups contained in the surface portion of the porous film Similar to the above item (2), two samples of the porous film were prepared, and the hydroxyl group and the carboxyl group were labeled, respectively. Then, the content D was calculated by the same method as the above item (3).

[0050] B. Glass transition temperature A styrene-butadiene rubber aqueous solution was dried at 120°C to obtain a styrene-butadiene rubber sheet having a thickness of 50 µm. Based on the tensile vibration-non-resonance method of IS K7244 (1998) (this is called the dynamic viscoelasticity method), the temperature vs. loss tangent curve was measured using the styrene-butadiene rubber sheet as a sample with a dynamic viscoelasticity measuring device DMS6100 manufactured by Seiko Instruments Inc., and the temperature at which the loss tangent showed a maximum value was determined as the glass transition temperature. The details of the measurement conditions are as follows.

[0051] When measuring the glass transition temperature of the styrene-butadiene rubber in the laminate, the laminate was immersed in toluene to dissolve the styrene-butadiene rubber in toluene, and then the porous film and the porous support were removed. Then, the toluene was volatilized and removed from the toluene solution in which the styrene-butadiene rubber was dissolved to prepare a styrene-butadiene rubber sheet, and the glass transition temperature was measured in the same manner as above. Measurement mode: Tensile Chuck distance: 20mm Sample width: 10mm Frequency: 1Hz ·Distortion amplitude: 10μm Initial force amplitude: 40mN Measurement temperature: -100℃ to 100℃ Heating rate: 5℃ / min Loss tangent: (Loss modulus) / (Storage modulus).

[0052] C. Average pore size The average pore size of the porous film was measured by the wet pressure / dry pressure method using a perm porometer "CFP-1500 (PMI)" under the following conditions and analysis method. Test solution: Galwick (15.9DYNES / CM) Measurement pressure: 500~2700kPa ·Analysis method: The average flow rate pressure was read from the obtained pressure / flow rate curve and used as the average pore size of the sample.

[0053] D. Thickness The porous film was allowed to stand for 24 hours in an atmosphere with a temperature of 20°C and a humidity of 65% RH, after which the thickness (μm) at five points was measured using a measuring device (Model ID-112, manufactured by Mitutoyo Corporation), and the average value was taken as the thickness of the porous film.

[0054] E. Metsuke The basis weight of the porous film, the porous support, or the laminate consisting of the porous film and the porous support was measured by the following method. First, five 100 mm square samples were prepared and left to stand for 24 hours in an atmosphere with a temperature of 20°C and a humidity of 65% RH. After that, the mass (g) of each of the five samples was measured and the average value was calculated as 1 m 2 Mass per unit (g / m 2 ) and basis weight (g / m 2 In addition, the basis weight of the materials constituting the laminate, such as styrene butadiene rubber, other than the porous film and the porous support, was calculated by subtracting the basis weights of the porous film and the porous support from the basis weight of the laminate.

[0055] F. Porosity The porosity of the porous film was calculated by the thickness obtained in D, the basis weight obtained in E, and the specific gravity of polyethylene (0.99 g / cm 3 The calculation was performed using the following formula:

[0056] Porosity (%) = (thickness - basis weight / 0.99) / thickness x 100.

[0057] G.Aperture ratio The surface of the porous support was observed with an optical microscope, and the obtained surface image was binarized to determine the aperture ratio. Specifically, the surface of the porous support was observed at 25 times magnification to obtain a surface photograph. Next, the image analysis software ImageJ (1.47V) (National Institutes of Health, USA) was used to read the surface photograph as an 8-bit image, and automatic binarization processing was performed to color-code the aperture and non-aperture parts. From the obtained image, the ratio of the number of pixels in the aperture part to the sum of the number of pixels in the aperture and non-aperture parts was calculated, and the aperture ratio (%) of the porous support was calculated.

[0058] H. Identification of surfactant composition The infrared absorption spectrum of the porous film was measured using a Fourier transform infrared spectrophotometer "IR Prestige-21 (Shimadzu Corporation)" and the peak derived from polyoxyethylene alkyl ether (1120 to 1110 cm -1 , 1350cm -1, 1290cm -1 , 1250cm -1 , 950cm -1 The composition of the surfactant was identified based on the following:

[0059] · Unit: ATR method unit (MIRacleA) Measurement wave number: 400~4000cm -1 In addition, when it was difficult to identify the surfactant composition by infrared absorption spectrum measurement alone, the porous film was measured by pyrolysis gas chromatography mass spectrometry (pyrolysis GC-MS), and the components were identified from the molecular weight / valence (m / z) information of fragment ions other than those attributable to polyethylene and the above-mentioned infrared absorption spectrum information.

[0060] I. Reduction rate of surfactant After the porous film was immersed in hot water at 80°C for 100 hours, the infrared absorption spectrum was measured in the same manner as in Section H above, and the reduction rate of the surfactant was determined as the percentage reduction in the peak area derived from the surfactant obtained relative to the peak area obtained by the method described in Section H above.

[0061] J. Ion Permeability and Durability of Ion Permeability The measurement was performed using an impedance analyzer. Specifically, a cell filled with a 30% potassium hydroxide aqueous solution was divided into two compartments by the laminate of the present invention, and the measurement was performed by an AC impedance method using Ni plates as electrodes. The value at which the plot on the obtained complex plane intersected with the x-axis (real axis) was determined, and the difference from the value measured without the laminate was taken as the impedance (mΩ) of the laminate. The smaller the impedance, the better the ion permeability. In addition, the durability of the ion permeability was measured by immersing the laminate in a 30% potassium hydroxide aqueous solution and holding it at 90°C for 24 hours, and then removing the laminate using tweezers, and using an impedance analyzer, the measurement was performed in the same manner as above. ·Measurement temperature: 60℃ Applied voltage: 10mV Frequency range: 100Hz~100kHz.

[0062] K. Gas shielding properties Measurements were performed according to the bubble point test method specified in JIS K 3832 (1990). Ion-exchanged water was used as the solvent, and the pressure was increased at 20 kPa / min. The pressure at which continuous bubbles were observed to appear from the laminate was read as the gas shielding pressure (kPa). The higher the gas shielding pressure, the better the gas shielding properties.

[0063] L. Durability of interlayer adhesion The laminate was immersed in a 30% potassium hydroxide aqueous solution and held at 90°C for 24 hours, and the state of the laminate after that and the behavior when the laminate was removed with tweezers were visually observed, and the durability of the interlayer adhesion was evaluated according to the following criteria a to c. The durability of the interlayer adhesion was judged to be a, the highest, b or higher was practical, and c was not practical.

[0064] a: When removed from the potassium hydroxide solution, the fabric did not peel off and maintained the laminated state before immersion. b: When immersed in an aqueous potassium hydroxide solution, the fabric does not peel off, but when removed with tweezers, the fabric peels off. c: Peeling of the fabric occurs during immersion in the potassium hydroxide solution.

[0065] [Example 1] As a porous film, a porous polyethylene film (weight: 6.7 g / m 2 A 12 μm thick SiO2 film was prepared, with a porosity of 43% and a pore diameter of 33 nm.

[0066] The polyethylene porous film was placed in a reaction vessel, and the reaction vessel was evacuated to create a vacuum inside. Then, oxygen gas (O 2 ) / Fluorine gas (F 2 ) / Nitrogen gas (N 2After introducing a mixed gas with a partial pressure of 0.3 / 0.1 / 0.6 atm, the reaction vessel was left at room temperature (23°C) for 30 seconds to expose the mixed gas to the polyethylene porous film, after which the atmosphere in the reaction vessel was replaced with nitrogen gas and the substrate was removed from the reaction vessel.

[0067] Next, the polyethylene porous film was immersed in a 0.05% by mass aqueous solution of polyoxyethylene alkyl ether (registered trademark of Daiichi Kogyo Seiyaku Co., Ltd.) as a surfactant for 10 seconds, then immersed in pure water for 60 seconds, and dried in an oven at 60° C. for 1 minute to obtain a porous film. The composition and physical properties of the obtained porous film are shown in Table 1.

[0068] Next, a polyphenylene sulfide woven fabric (120 g / m2) was used as a porous support. 2 Two sheets of the porous film (100% polyester, 40% opening ratio) were prepared, and both sheets were impregnated with a 5% aqueous solution of styrene-butadiene rubber (glass transition temperature of styrene-butadiene rubber: -58°C). One sheet of the fabric was then bonded to each side of the porous film, and the resulting mixture was dried at 80°C for 10 minutes to obtain a laminate of porous support / porous film / porous support. The physical properties of the resulting laminate are shown in Table 1.

[0069] [Comparative Example 1] A porous film was obtained in the same manner as in Example 1, except that the operation of immersing the porous film in the aqueous surfactant solution was changed to immersion in pure water for 600 seconds. The structure and physical properties of the obtained porous film and the physical properties of the laminate obtained using the porous film are shown in Table 2.

[0070] [Comparative Example 2] Except for not exposing the porous film to the mixed gas, a hydrophilic porous film was obtained in the same manner as in Example 1. The structure and properties of the obtained porous film and the properties of the laminate obtained using the porous film are shown in Table 2.

[0071] [Example 2] A porous film was obtained in the same manner as in Example 1, except that the exposure time to the mixed gas was 15 seconds, the concentration of the aqueous surfactant solution was 0.10 mass%, and the immersion time in the aqueous surfactant solution was 30 seconds. The configuration and physical properties of the obtained porous film and the physical properties of the laminate obtained using the porous film are shown in Table 1.

[0072] [Comparative Example 3] A porous film was obtained in the same manner as in Example 2, except that the immersion time in the aqueous surfactant solution was 10 seconds. The structure and physical properties of the obtained porous film and the physical properties of the laminate obtained using the porous film are shown in Table 2.

[0073] [Example 3] A porous film was obtained in the same manner as in Example 1, except that a styrene-butadiene rubber having a glass transition temperature of −28° C. was used. The structure and physical properties of the obtained porous film and the physical properties of the laminate are shown in Table 1.

[0074] [Comparative Example 4] A porous film was obtained in the same manner as in Example 1, except that the aqueous solution of styrene-butadiene rubber was changed to a hot melt consisting of styrene-isoprene-styrene and applied to the woven fabric. The structure and physical properties of the obtained porous film and the physical properties of the laminate are shown in Table 2.

[0075] [Comparative Example 5] As a porous film, a porous polyethylene film (weight: 6.7 g / m 2 A porous film (12 μm thick, porosity 43%, pore size 33 nm) was irradiated with an electron beam to graft-polymerize acrylic acid monomers. The basis weight of the graft-polymerized components attached to this porous film was determined to be 3.3 g / m2 based on the change in weight before and after graft polymerization. 2 Then, a laminate was obtained in the same manner as in Example 1 using the same binder and porous support as in Example 1. The configuration and physical properties of the obtained porous film and the physical properties of the laminate are shown in Table 2.

[0076] [Example 4] A porous film was obtained in the same manner as in Example 1, except that the exposure time to the mixed gas was 15 seconds and the immersion time in the surfactant aqueous solution was 60 seconds. The structure and physical properties of the obtained porous film and the physical properties of the laminate obtained using the porous film are shown in Table 1.

[0077] From the comparison of Example 1 with Comparative Examples 1 and 2, and from the comparison of Example 2 with Comparative Example 3, it is found that the ratio (content B / content A) of the content B of the hydrophilic group contained in the entire porous film to the content A of the carbon atoms contained in the entire porous film is larger than the ratio (content D / content C) of the content D of the hydrophilic group in the surface portion constituting both sides of the hydrophilic porous film to the content C of the carbon atoms in the surface portion constituting both sides of the hydrophilic porous film, and the content B / content A is 0.03 to 0.20, and the content D / content C is 0.01 to 0.10, thereby forming a laminate having high ion permeability. From the comparison of Example 1 with Example 4, it is found that good ion permeability can be obtained by the content B / content A being within a preferred range. From the comparison of Example 1 with Comparative Example 5, it is found that the laminate of the present invention has durability of ion permeability. Comparing Examples 1 and 3 with Comparative Example 4, it is clear that bonding with the styrene-butadiene rubber of the present invention provides durable interlayer adhesion, and that this effect is remarkable when the glass transition temperature of the styrene-butadiene rubber is -30°C or lower.

[0078] [Table 1]

[0079] [Table 2] [Industrial Applicability]

[0080] The laminate of the present invention has high ion permeability, and also has durability of ion permeability and shape retention even in a high-temperature and high-concentration alkaline aqueous solution, and can therefore be suitably used as a diaphragm for alkaline water electrolysis.

Claims

1. A laminate in which a porous film made of polyethylene and a porous support mainly composed of polyarylene sulfide are bonded, the porous film has a surface and a pore surface, and hydrophilic groups containing at least one of hydroxyl groups and carboxyl groups are chemically bonded to polyethylene, the ratio of the content B of the hydrophilic groups contained in the entire porous film to the content A of carbon atoms contained in the entire porous film (content B / content A) is greater than the ratio of the content D of the hydrophilic groups in the surface portions constituting both sides of the porous film to the content C of carbon atoms in the surface portions constituting both sides of the porous film (content D / content C), the ratio (content B / content A) is 0.03 to 0.20, and the ratio (content D / content C) is 0.01 to 0.10, and the porous support and the porous film are bonded with styrene-butadiene rubber.

2. The laminate according to claim 1, characterized in that the porous film contains a surfactant, and the reduction rate of the surfactant is 10% or less before and after immersing the porous film in hot water at 80°C for 100 hours.

3. 3. The laminate according to claim 2, wherein the surfactant is a polyoxyalkylene alkyl ether.

4. The laminate according to any one of claims 1 to 3, characterized in that the styrene-butadiene rubber has a glass transition temperature of -30°C or lower.

Citation Information

Patent Citations

  • Electrolytic diaphragm

    JP2014148708A

  • Electrolytic diaphragm

    JP2014148709A